2016
DOI: 10.1111/aas.12813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugammadex vs. pyridostigmine–glycopyrrolate on post‐operative nausea and vomiting: propensity score matching

Abstract: Sugammadex might be more beneficial for PONV compared to pyridostigmine-glycopyrrolate mixture for patients who have received opioid-based IV-PCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…A meta‐analysis of 17 randomised trials involving 1553 patients reported that the relative risk of nausea after sugammadex was 0.94 (95%CI 0.79–1.13), and of vomiting 0.87 (95%CI 0.67–1.17 . Since this systematic review, several small studies have suggested that PONV may be transiently reduced in the first hour or so after reversal with sugammadex, although not subsequently . This positive finding is consistent with previous data but the quality of evidence is low, because all studies have been either retrospective cohort studies or small clinical trials with poor bias control such as inadequate blinding or power, or only positive findings for a secondary outcome.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…A meta‐analysis of 17 randomised trials involving 1553 patients reported that the relative risk of nausea after sugammadex was 0.94 (95%CI 0.79–1.13), and of vomiting 0.87 (95%CI 0.67–1.17 . Since this systematic review, several small studies have suggested that PONV may be transiently reduced in the first hour or so after reversal with sugammadex, although not subsequently . This positive finding is consistent with previous data but the quality of evidence is low, because all studies have been either retrospective cohort studies or small clinical trials with poor bias control such as inadequate blinding or power, or only positive findings for a secondary outcome.…”
Section: Introductionsupporting
confidence: 86%
“…These findings are in contrast with those of several previous studies. Lee et al in a large retrospective study (with propensity score matching to improve comparability) found lower frequency and severity of PONV after sugammadex reversal compared with pyridostigmine/glycopyrrolate reversal . In a randomised double‐blind trial of patients having extremity surgery without PONV prophylaxis by Koyuncu et al , PONV scores were lower on arrival in the recovery room following sugammadex, but the incidence of PONV in the first 24 h was high and did not differ significantly between sugammadex and neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…Increased heart rate and cardiac output may reduce hypotensive episodes, thus hypotension induced PONV [17]. As cholinergic receptors are distributed in the GI tract, as well as in the brain, glycopyrrolate may block cholinergic receptors in the GI tract, resulting in reduced gastric secretion and intestinal movement [11,28]. These mechanisms of glycopyrrolate may decrease the incidence of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were as follows: 1) patients who received re-operation on the same site, 2) patients who participated in other randomized controlled trials, 3) patients who received sugammadex as reversal agents, and 4) missing data. Patients who used sugammadex as a reversal agent were excluded due to the potential effect of sugammadex on PONV which was discussed in a study by Lee et al [11].…”
Section: Methodsmentioning
confidence: 99%
“…[7,21] An advantage of sugammadex for PONV has also been reported by several studies. [8,22,23] Cholinergic effects from the use of cholinesterase inhibitors can cause a decrease in oesophageal tone, and an increase in secretion and intestinal movement that might be associated with the increased PONV. However, due to the fear of these potential side effects, anticholinergic agents have been used to compensate for these unwanted cholinergic effects.…”
Section: Discussionmentioning
confidence: 99%